When at rest: "Event-free" active inference may give rise to implicit self-models of coping potential. (2nd September 2015) - Murray, Ryan J.; Gerrans, Philip; Brosch, Tobias; Sander, David
Abstract: Kalisch and colleagues highlight coping potential (CP) as a principle resilience mechanism during event engagement. We complement this discussion by exploring generative implicit CP self-models, arguably emerging during "resting-state, " subsequent and prior to events. Resting-state affords a propitious environment for Bayesian learning, wherein appraisals/reappraisals may update active inferential CP self-models, which then mediate appraisal style organization and resilience factor valuation.